PENGEMBANGAN USAHA KELOMPOK PETERNAK BURUNG PUYUH - Dimas Pratidina Puriastuti H.; Ari Brihandhono (Publisher UPT P2M Politeknik Negeri Malang, 2017)
This devotion for groups breeder quail aims to provide a solution on efforts to improve the knowledge and skills of farmers in the utilization and processing technology potential of natural resources as feed material quail, then capable and skilled in technology breeding, utilization of waste quail eggs culled as catfish and processing technology manure into organic fertilizer, so it will be able to increase revenue, independence and well-being of farmers. The method used is the discussion, training, demplot, mentoring and evaluation as well as involving students in the program so as to provide a solution to resolve the problems faced by farmers groups quail partners. This results show that the public response quail farmers are very good and enthusiastic for proactive follow the program in all the activities for outreach, training, demoplot, mentoring and evaluation. The existence of this service program had a positive impact on the environment ie partners provide solutions or alternative solutions to problems faced by the farmers in the village and surrounding communities.